History of San Pablo reviewed, rewritten, and retold - Alip, Jaime Aristotle B.; Boncocan, Rhina A.; Meneses, Eileen; Garilao, Maria Karina V.; De Jesus, Armando F.; Rivera, Cynthia Luz P.; Sy, Nicholas Michael C.; Gealogo, Francis A. (San Pablo City, Laguna Center for Agriculture and Rural Development (CARD), Inc., 2016)
The essays included in this compendium formed part of the project supported by CARD in their continuing efforts at building the local community's sense of identity and self worth. Since San Pablo is the locale where CARD initially made its significant mark before it expanded to other localities within the Philippines and beyond, it was but expected that a local history of San Pablo would be the focus of CARD's first book project on local history.
Editor's introduction -- Reflection on the religious history of San Pablo de los Montes during the Spanish colonial period -- San Pablo's history of wine and oil : Four narratives taken from archival manuscripts -- What else were las hijas de San Pablo doing?! -- Population, peace and public order in San Pablo during the nineteenth century -- Moneylending, usury, and sanlang bili in 19th century San Pablo -- CARD MRI and its journey of transformation and empowerment from San Pablo and beyond -- The future of our past : local history studies for San Pablo and beyond -- Glossary -- About the authors